(untitled) (Health Renaissance, 2017)
Background: A prescription is standard form that is used by doctors to prescribe medicines. A prescription done ideally include some demographic profile and detail instructions of what medicines should be given to whom, what formulations, how much doses, by which route, when, how frequently and for how long. The rational drugs prescribing and prescription writing is important in patient care. The incomplete prescription and irrational drugs would be harmful to patient. The WHO has defined rational use of medicines as requiring that “patients receive medications appropriate to their clinical needs, in doses that meet their own requirements for an adequate period of time at the lowest cost to them and their community.” Assessment of prescription pattern helps in formulating prescribing policies of the institution. Objective: The study aims to finding out the prescription writing skill on the base rational drug prescribing in GOPD, BPKIHS. Method: A cross sectional study was conducted in GOPD, BPKIHS, in two week period from 13th July 2012 to 27th July 2012. A semi structured questionnaire was used to document difficult variables and interviewing the patients. A total number of 100 prescriptions were analyzed and the same number determined. Results: The number of male and female patients was 57 and 43 respectively. The minimum age recorded was 15 and maximum age 85. The mean age was 38.64 ±18.702 (range 15-85 years). General physical examination and systemic examination were mentioned in 63 and 72% cases respectively. Likewise 91 % cases were advised for laboratory investigations. Provisional and final diagnoses were mentioned in 49% and 54% respectively. Forty-six patients were treated on empirical basis. Six percent of patients were prescribed more 5 items, 18% patients. 4 items and 36 % patients were prescribed 3 items of drugs. Only 31% patients were prescribed 2 items of drugs that would meet the criteria of World Health Organization guide to prescription. Common side effects of prescribed drugs were not mentioned in 84 patients. Drug prescribing in the GOPD of BPKIHS is not as per the WHO guidelines with many missing important details. Seventeen percent of patients had no recall, only 29% of patients had excellent recall for how to take prescribed medicines. In 51% patients special advises related with prescribed drugs were provided. The follow up visit was mentioned in 78% patients. Seventy percent patients did not known the name of treating doctors and 58% patients were happy with the doctor’s consultation. Conclusion: A majority of the doctors were not able to correctly define rational drugs prescribing and there is missing many important details in prescription writing. Therefore an educational intervention regarding the rational drug prescribing and prescription writing skills should be carried out in all doctors working in GOPD. Health Renaissance 2015;13(2): 72-79